Math, asked by mjain0608, 3 months ago

prove the following question...​

Attachments:

Answers

Answered by tuhingenius2006
1

Answer:

2(sin6θ + cos6θ) - 3 (sin4θ + cos4θ) + 1  

=2[(sin2θ)3 + (cos2θ)3] -3[(sin2θ)2 + (cos2θ)2]+1

=2[(sin2θ + cos2θ)3 -3sin2θcos2θ (sin2θ + cos2θ)] -3[(sin2θ + cos2θ)2

-2sin2θcos2θ]+1

The algebraic identity

a3 + b3 = (a+b)3 - 3ab(a+b) and  

a2 + b2 = (a+b)2 - 2ab

are used in the above step where

a = sin2θ and b = cos2θ.

writing sin2θ + cos2θ = 1, we have  

= 2[1-3 sin2θ cos2θ] -3[-2 sin2θcos2θ] + 1

= 2-6 sin2θcos2θ -3 + 6 sin2θcos2θ + 1

= -3+3=0              

HOPE U LIKE IT PLZ MARK IT AS THE BRAINLIEST

Answered by mathdude500
3

\large\underline{\sf{Given \:Question - }}

Prove the following :

\rm :\longmapsto\:2( {sin}^{6}\theta  +  {cos}^{6}\theta  ) + 1 = 3( {sin}^{4}\theta   +  {cos}^{4}\theta  )

\large\underline{\sf{Solution-}}

\rm :\longmapsto\:2( {sin}^{6}\theta  +  {cos}^{6}\theta  ) + 1

can be rewritten as

\rm \:  =  \: 2\bigg( {( {sin}^{2} \theta  )}^{3}   +  {( {cos}^{2} \theta  )}^{3} \bigg)  + 1

We know,

\boxed{ \bf{ \:  {x}^{3} +  {y}^{3} =  {(x + y)}^{3} - 3xy(x + y)}}

So, using this identity, we get

\rm \:  =  \: 2\bigg( {( {sin}^{2}\theta   +  {cos}^{2} \theta  ) }^{3} - 3 {sin}^{2} \theta   {cos}^{2} \theta  ( {sin}^{2} \theta   +  {cos}^{2} \theta  ) \bigg)  + 1

We know,

\boxed{ \bf{ \:  {sin}^{2}x +  {cos}^{2}x = 1}}

So, using this identity, we get

\rm \:  =  \: 2\bigg( {( 1 ) }^{3} - 3 {sin}^{2} \theta   {cos}^{2} \theta  ( 1  ) \bigg)  + 1

\rm \:  =  \: 2\bigg( 1 - 3 {sin}^{2} \theta   {cos}^{2} \theta \bigg)  + 1

\rm \:  =  \: 2 - 6{sin}^{2} \theta   {cos}^{2} \theta   + 1

\rm \:  =  \: 3 - 6{sin}^{2} \theta   {cos}^{2} \theta

\rm \:  =  \: 3(1 - 2{sin}^{2} \theta   {cos}^{2} \theta)

\rm \:  =  \: 3 \bigg( {(1)}^{2}  - 2{sin}^{2} \theta   {cos}^{2} \theta \bigg)

We know,

\boxed{ \bf{ \:  {sin}^{2}x +  {cos}^{2}x = 1}}

So, Replace 1 by this identity, we get

\rm \:  =  \: 3 \bigg( {( {sin}^{2}\theta   +  {cos}^{2}\theta    )}^{2}  - 2{sin}^{2} \theta   {cos}^{2} \theta \bigg)

We know,

\boxed{ \bf{ \:  {(x + y)}^{2} =  {x}^{2} +  {y}^{2} + 2xy}}

\rm \:  =  \: 3 \bigg( {sin}^{4}\theta   +  {cos}^{4}\theta + \cancel{ 2 {sin}^{2}\theta   {cos}^{2}\theta} -  \cancel{2{sin}^{2} \theta   {cos}^{2} \theta} \bigg)

\rm \:  =  \: 3 \bigg( {sin}^{4}\theta   +  {cos}^{4}\theta  \bigg)

Hence,

\rm :\longmapsto\:\boxed{ \bf{ \: 2( {sin}^{6}\theta  +  {cos}^{6}\theta  ) + 1 = 3( {sin}^{4}\theta   +  {cos}^{4}\theta  )}}

Additional Information:-

Relationship between sides and T ratios

sin θ = Opposite Side/Hypotenuse

cos θ = Adjacent Side/Hypotenuse

tan θ = Opposite Side/Adjacent Side

sec θ = Hypotenuse/Adjacent Side

cosec θ = Hypotenuse/Opposite Side

cot θ = Adjacent Side/Opposite Side

Reciprocal Identities

cosec θ = 1/sin θ

sec θ = 1/cos θ

cot θ = 1/tan θ

sin θ = 1/cosec θ

cos θ = 1/sec θ

tan θ = 1/cot θ

Co-function Identities

sin (90°−x) = cos x

cos (90°−x) = sin x

tan (90°−x) = cot x

cot (90°−x) = tan x

sec (90°−x) = cosec x

cosec (90°−x) = sec x

Fundamental Trigonometric Identities

sin²θ + cos²θ = 1

sec²θ - tan²θ = 1

cosec²θ - cot²θ = 1

Similar questions